2019
DOI: 10.3390/molecules24061175
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of New Quinoxaline Derivatives as Anticancer Agents and Apoptotic Inducers

Abstract: The quinoxaline scaffold is a promising platform for the discovery of active chemotherapeutic agents. Three series of quinoxaline derivatives were synthesized and biologically evaluated against three tumor cell lines (HCT116 human colon carcinoma, HepG2, liver hepatocellular carcinoma and MCF-7, human breast adenocarcinoma cell line), in addition to VEGFR-2 enzyme inhibition activity. Compounds VIId, VIIIa, VIIIc, VIIIe and XVa exhibited promising activity against the tested cell lines and weak activity agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 33 publications
(48 reference statements)
0
31
0
Order By: Relevance
“…The antitumor activity of kinase inhibitors comprising diaryl urea has earned immense attention because of its binding mode. Owing to its beneficial anticancer properties, Abouzid et al [ 60 ] synthesized an array of quinoxaline-based compounds with amide, urea, thiourea, and sulfonamide moieties. Quinoxalines is derived from the reaction of o-phenylenediamine and α-keto-carboxylic acids [ 61 ].…”
Section: Synthetic Pathways To Prepare Biologically Active Quinoxamentioning
confidence: 99%
See 1 more Smart Citation
“…The antitumor activity of kinase inhibitors comprising diaryl urea has earned immense attention because of its binding mode. Owing to its beneficial anticancer properties, Abouzid et al [ 60 ] synthesized an array of quinoxaline-based compounds with amide, urea, thiourea, and sulfonamide moieties. Quinoxalines is derived from the reaction of o-phenylenediamine and α-keto-carboxylic acids [ 61 ].…”
Section: Synthetic Pathways To Prepare Biologically Active Quinoxamentioning
confidence: 99%
“…The C2 chlorine is replaced by an ether linkage affixed to a benzene ring having a free aldehyde or amine group. The reaction Scheme 18, expounds the synthetic pathway to prepare 4-(2-methyl quinoxaline-3-yloxy)benzaldehyde (60) and N-((4-(2-methylquinoxaline-3yloxy)phenyl)methylene)-4-substituted benzenamine (63) using 2-chloro-3-methyl quinoxaline (59). A mixture of ( 59) and 4-hydroxy benzaldehyde was refluxed in acetonitrile for 30 h to afford (60) as an intermediate.…”
Section: Synthesis Of 4-(2-methyl Quinoxaline-3-yloxy)benzaldehyde and N-((4-(2-methylquinoxaline-3-yloxy)phenyl)methylene)-4-substitutedmentioning
confidence: 99%
“…Quinoxaline and quinazoline and their derivatives are considered as important synthetic targets in anticancer drug discovery [ 19 , 20 , 21 , 22 , 23 , 24 ]. Quinazoline derivatives have been reported to exhibit cytotoxic activity against different cancer types via various mechanisms, including the inhibition of; epidermal growth factor receptor (EGFR) [ 25 ], or kinesin spindle protein (KSP) [ 26 ], interfering with: Wnt signaling pathway [ 27 ] and phosphatidylinositol-3-kinase (PI3K) [ 28 ], in addition to the downregulation of the antiapoptotic proteins Bcl2 and BclxL [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, quinoxaline derivatives were studied as anticancer agents and apoptotic inducers against three lines of cancer cells, HCT116, HepG1, and MCF-7. The lead compound was found to cause a noticeable disruption in the cell cycle profile, and induced cell cycle arrest at the G2/M phase boundary [ 20 ]. On the other hand, in the investigation on antiproliferative activity of aminophosphonates by Huang et al, the authors concluded that the most promising derivative may induce apoptosis of SK-OV-3 cells through mitochondrion pathways [ 21 ].…”
Section: Introductionmentioning
confidence: 99%